Analisis Resepsi Citra Diri Jessica Wongso dalam Film Dokumenter "Ice Cold: Murder, Coffee and Jessica Wongso" - Nirmala, Dewi Permata; Jokhanan Kristiyono (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This study is entitled Analysis of Jessica Wongso's Self-Image Reception in the Documentary Film "Ice Cold: Murder, Coffee, and Jessica Wongso" which is the background of this study is that film is one form of mass media and the documentary film "Ice Cold: Murder, Coffee and Jessica Wongso" presents another perspective on the controversial case of Jessica Wongso and how she is depicted, different from the representation of the mass media in 2016 which gave rise to various perceptions among the public. Reviewed and connected with Stuart Hall's reception theory on the study of meaning or acceptance. The purpose of this study is to find out how the analysis of Jessica Wongso's self-image reception in the documentary film "Ice Cold: Murder, Coffee and Jessica Wongso". This type of research is qualitative descriptive with a reception analysis research method. The observation unit in this study is the documentary film "Ice Cold: Murder, Coffee and Jessica Wongso". The data collection technique used is FGD (Focus Group Discussion). The data validity checking technique used is the extension of participation, observer persistence and triangulation. Data analysis in this study is data reduction, data presentation and drawing conclusions. It can be concluded that the documentary film "Ice Cold: Murder, Coffee and Jessica Wongso" effectively presents various perspectives on the Jessica Wongso case. The results of the study also highlight the importance of understanding how the media shapes and influences public perceptions of the depiction of the self-image of figures such as Jessica Wongso in controversial cases and her involvement in views on justice and the justice system. The results of the discussion in the decoding process were that the majority of participants were in the Dominant Hegemonic Position.